Rodné mestečko : Zobrané poviedky II. zv.: 1969-1988 - Sloboda, Rudolf, 1938-1995 (Koloman Kertész Bagala L.C.A, 2006)
Druhý zväzok Slobodových zobraných poviedok zahŕňa poviedky z rokov 1969 až 1988: